Facies and evaporite genesis of the Kuscular Formation (Lower Paleocene) saline playa complex, Eastern Turkey - Türkmen, I (Pergamon-Elsevier Science Ltd, 2004)
The Kuscular Formation (Lower Paleocene), located in Eastern Turkey, is an alluvial and playa foreland basin succession deposited in a semi-arid climate. The playa deposits of the Kuscular Formation, composed of interbedded green sandstone-siltstone-mudrock, gypsiferous sandstone, red-green gypsiferous mudrock, and banded nodular secondary gypsum, are found among the distal alluvial fan deposits. Interbedded green sandstone-siltstone-mudrock with desiccation cracks are interpreted as dry mudflat-sandflat deposits. The banded nodular secondary gypsum and gypsiferous mudrocks, which contain desiccation cracks, are interpreted as a saline playa and saline mudflat. Distal alluvial fan deposits are represented by stratified conglomerate and stratified pebbly sandstone. The sulfur in the evaporites was very likely derived from the oxidation of sulfides in Upper Cretaceous magmatic rocks comprising the basement of the basin. Soft sediment deformation structures (slump folds), which indicate seismically active areas, were formed within the playa and dry mudflad-sandflat complex. The facies aspects of playa deposits would suggest that the climate in Turkey was semi-arid during the Early Paleocene. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: evaporites; gypsum; saline playa; Turkey